Ceramics and the Spanish Conquest : Response and Continuity of Indigenous Pottery Technology in Central Mexico (2011)
Focusing on the native ceramic technology of central Mexico during the early colonial period and the present-day, this book offers a refreshing view into the process of cultural continuity and change in the indigenous Mesoamerican world after the Spanish conquest. Readership: All those interested in sixteenth century colonialism, the colonial period in Middle America, material culture, ancient and present-day ceramics, as well as in cultural continuity and change.